1997
DOI: 10.2337/diacare.20.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in the Incidence of Childhood IDDM in Israel (1965–1993): Marked increase since 1985, especially in Yemenite Jews

Abstract: Israel is a country with low, intermediate, and high incidence of childhood IDDM. The interethnic differences in incidence are probably due to genetic factors. However, the significant increase in incidence since 1985 in the Jewish population is ascribed to thus far unidentified environmental factors. It is hypothesized that the marked increase in IDDM is due to environmental factors linked to changes in affluence and lifestyle. These may also explain the difference in incidence between the Jewish and Arab pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 15 publications
2
24
1
Order By: Relevance
“…These studies have shown that there are wide variations in incidence between geographical areas or population groups. In recent years a marked increase in the incidence of childhood T1DM has been reported from many countries [Bingley and Gale, 1989;Joner and Sovik, 1989;Nystrom et al, 1990;Soltesz et al, 1990;Tuomilehto-Wolf and Akerblom, 1991;Schober et al, 1995;Shamis et al, 1997]. The highest incidences were found in Finland, Sardinia and the Yemenite Jews in Israel, and the lowest ones in the Far East.…”
Section: Initiation Of the Autoimmune Process Of Type 1 Diabetes Begimentioning
confidence: 97%
“…These studies have shown that there are wide variations in incidence between geographical areas or population groups. In recent years a marked increase in the incidence of childhood T1DM has been reported from many countries [Bingley and Gale, 1989;Joner and Sovik, 1989;Nystrom et al, 1990;Soltesz et al, 1990;Tuomilehto-Wolf and Akerblom, 1991;Schober et al, 1995;Shamis et al, 1997]. The highest incidences were found in Finland, Sardinia and the Yemenite Jews in Israel, and the lowest ones in the Far East.…”
Section: Initiation Of the Autoimmune Process Of Type 1 Diabetes Begimentioning
confidence: 97%
“…For example, the incidence in the Nordic countries (Finland, Sweden, and Norway) is 2-4 times higher than that in Estonia (3,4,13,14) and 2-3 times higher than that in Iceland (15). Large interethnic differences in the incidence rates between Jewish and Arab populations have been reported in Israel (16). Geographical variation in incidence appears to reflect the global distribution of major ethnic populations, which demonstrates a different degree of genetic susceptibility to diabetes among populations.…”
mentioning
confidence: 99%
“…There is, however, a notable variation among Israel's different ethnic groups, which has been attributed to differences in genetic or environmental factors (7). Among these groups, the Yemenites are unique, having the highest incidence of type 1 diabetes (18.5/100,000) compared with the overall Jewish population (5.7/100,000) (8).…”
mentioning
confidence: 99%